Improving asphalt resistance to aging by using waste tyre rubber / Asim Hassan Ali, Nuha S. Mashaan and Mohamed Rehan Karim - Ali, Asim Hassan; Mashaan, Nuha S.; Karim, Mohamed Rehan (2012)
In recent times, a serious problem that leads to environmental pollution is the abundance and increase of waste tyre disposal. Large amount of rubber is used as tyres for cars and trucks etc. Despite the long run in service, these tyres are not discarded. The major approach to solve this issue is the recycle and reuse of waste tyre rubber, and the reclaimation of rubber raw materials. This research aims to investigate the effects of crumb rubber modifier concentration on the rheological and physical properties of rubberised bitumen after aging. In order to evaluate the durability performance of rubberised bitumen, aging tests have been conducted using short-term aging (i.e., rolling thin film oven test or RTFOT) and long-term aging (i.e., pressure aging vessel or PAV). The results showed that the use of rubberised bitumen binder reduced the aging effect on physical and rheological properties of the bitumen binder as illustrated through lower aging index of viscosity.